Raman spectra of planar supported lipid bilayers. - Lee, C; Bain, C (2005)
Raman scattering has been used to obtain high quality vibrational spectra of planar supported lipid bilayers (pslb's) at the silica/water interface without the use of resonance or surface enhancement. A total internal reflection geometry was used both to increase the bilayer signal and to suppress the water background. Polarization control permits the determination of four components of the Raman tensor, of which three are independent for a uniaxial film. Spectra are reported of the phospholipids DMPC, DPPC, and POPC, in the C-H stretching region and the fingerprint region. The temperature-dependent polarized spectra of POPC show only small changes over the range 14-41 degrees C. The corresponding spectra of DMPC and DPPC bilayers show large thermal changes consistent with a decreasing tilt angle from the surface normal and increasing chain ordering at lower temperatures. The thermal behavior of DMPC pslb's is similar to that of vesicles of the same lipid in bulk suspension. In contrast to calorimetry, which shows a sharp phase transition (L alpha-L beta') with decreasing temperature, the changes in the Raman spectra occur over a temperature range of ca. 10 degrees C commencing at the calorimetric phase transition temperature.